Reflections on critical reading as a need beyond the school environment - Castillo González, Floriluz; Pérez Rodríguez, Nidya Constanza (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The present article exposes the reflections and questions in front of a series of didactic strategies, designed with the intention of offering new experiences for the strengthening of the critical reading in students of ninth grade of an educational institution of Boyacá. Then the subject is approached with a registry of research works at the national level, which provide categorical elements on critical reading in school spaces. The methodology used is the educational research action and the classroom project, as a collaborative strategy for the study of didactic strategies in favour of the use of continuous and discontinuous texts. It approaches critical reading as a tool studied from Cassany (2006), Serrano and Madrid (2007) and Lipman (1998), with features focused on empowering secondary school students with skills of analysis, inference, reflection, critical thinking, creativity and evaluation of reading practice. As partial significant findings, the research finds the possibility of the constant investigation of teachers in the Spanish area, to reflect and understand the critical reading exercises beyond the school environment and the generation of dialogue spaces in the classroom, through confrontation and debate exercises.